2019
DOI: 10.3920/bm2017.0146
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum IM55 and Lactobacillus plantarum IM76 alleviate allergic rhinitis in mice by restoring Th2/Treg imbalance and gut microbiota disturbance

Abstract: This study aimed to examine whether probiotics, which suppressed the differentiation of splenic T cells into type 2 helper T (Th2) cells and induced into regulatory T cells in vitro, alleviate allergic rhinitis (AR) and gut microbiota disturbance. We isolated Bifidobacterium longum IM55 and Lactobacillus plantarum IM76 from human faecal microbiota and kimchi, respectively, and examined their effects on ovalbumin (OVA)-induced AR and gut microbiota disturbance in mice. Treatment with IM55, IM76, or their probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 56 publications
3
43
0
1
Order By: Relevance
“…studies reporting positive effects of administration with various probiotic Bifidobacterium spp. on the Treg/T effector cell balance in humans (Konieczna et al, 2012) and mice, which thereby ameliorate allergic and autoimmune diseases (Lyons et al, 2010;Zuo et al, 2014;Liu et al, 2018;Kim et al, 2019). Furthermore, a growing body of evidence suggests an important immunomodulatory role of hexa-acylated lipopolysaccharide (LPS), a major constituent of the outer membrane of Gammaproteobacteria, which exhibit superior Toll-like receptor 4 (TLR4) stimulatory capacity compared to the less acylated LPS present from other Gram-negative bacteria (Larsen et al, 2012(Larsen et al, , 2015Li et al, 2013;Brix et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…studies reporting positive effects of administration with various probiotic Bifidobacterium spp. on the Treg/T effector cell balance in humans (Konieczna et al, 2012) and mice, which thereby ameliorate allergic and autoimmune diseases (Lyons et al, 2010;Zuo et al, 2014;Liu et al, 2018;Kim et al, 2019). Furthermore, a growing body of evidence suggests an important immunomodulatory role of hexa-acylated lipopolysaccharide (LPS), a major constituent of the outer membrane of Gammaproteobacteria, which exhibit superior Toll-like receptor 4 (TLR4) stimulatory capacity compared to the less acylated LPS present from other Gram-negative bacteria (Larsen et al, 2012(Larsen et al, , 2015Li et al, 2013;Brix et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NVP-1703 is a probiotic mixture of B. longum IM55 (from the human gut bacteria collection) as a T-cell regulator and L. plantarum IM76 (from the fermented food bacteria collection) as a macrophage NF-κB inhibitor. We previously reported that NPV-1703 regulates innate and adaptive immunity in animal and in vitro studies [ 15 , 16 ]. In the present study, NVP-1703 treatment significantly improved TNSS and RCAT scores by increasing levels of IL-10, which corresponds to the anti-allergic effect of B. longum IM55 and L. plantarum IM76.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, open-label crossover study of Lactobacillus johnsonii EM1 in 7–12-year-old children with perennial AR, treatment with EM1 and levocetirizine combined significantly increased serum TGF-β levels compared with levocetirizine alone at week 12 [ 14 ]. We previously reported that the noble probiotic NVP-1703, a mixture of Bifidobacterium longum IM55 and Lactobacillus plantarum IM76, mitigated ovalbumin (OVA)- and house dust mite allergen (HDMA)-induced AR in mice, reducing IL-4, IL-5, IL-13, and IgE levels in nasal mucosa, bronchial alveolar lavage fluid, and blood and increasing the level of IL-10 [ 15 , 16 ], suggesting that probiotics may suppress Th2 response by promoting Treg activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that allergic symptoms can be alleviated by the intake of certain foods, components thereof, or probiotics such as tea (extracts of Camellia sinensis L.), catechin, lactic acid bacteria, and bifidobacteria (8,9). In particularly, tea catechins, a group of polyphenolic compounds like epigallocatechin-3-O-(3-O-methyl) gallate (EGCG3"Me) and epigallocatechin-3-O-(4-O-methyl) gallate (EGCG4"Me), exert strong anti-allergic effects (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%